From Advertising to Hyper-advertising: Semiotics, Narrative and Discourse - Yalán-Dongo, Eduardo (2016)
Advertising design is a discursive planning that does not only build an identity as brand value or graphic development, but also as Semiotics suggests, it produces a narrative level outlining the advertising story. The use of media, construction of characters, storytelling, organization of advertisement, are all expressions of this narrative level which in turn depends on a “context” or expression process from which they are built. This article aims to identify the different forms of narrative production in relation to three types of advertising discourse (Discourse Phase 1, Phase 2 and hyperadvertising) as well as evaluate its contrasts and expressions within the advertising communication and consumer society.